Eksistensi Partai Politik dan Degradasi Moral Bangsa - Insan Mahmud (Resolusi: Jurnal Sosial Politik, 2018)
In the political system in Indonesia, political parties are one of the pillars of democracy. As the only institutional framework for the process of representation and governance, political parties are required to be more proactive in creating conditions and possibilities for fundamental change in the political, economic and cultural nations of the nation. So the great task for the elite of political parties is to show the existence of political parties as the institution most responsible for the nation's moral upholding. The problem that often arises is the moral degradation shown by the rampant cases of corruption and other cases. This paper dictates the importance of oversight by political parties over the political power of the executive, legislative and judiciary. This assumption is built on the premise that leaders in a country are a product of recruitment and regeneration by political parties.